2004
DOI: 10.1021/jp0494990
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding of Water in Aqueous Solutions of Trimethylamine-N-oxide and tert-Butyl Alcohol:  A Near-Infrared Spectroscopy Study

Abstract: The hydration properties of two biologically relevant molecules, trimethylamine-N-oxide (TMAO) and tertbutyl alcohol (TBA), were investigated by monitoring the effects of these two solutes on the near-infrared (NIR) spectra of water. In particular, the 1450-nm ν 1 + ν 3 water combination band (ν 1 is the symmetric stretching and ν 3 is the asymmetric stretching) and the 1928-nm ν 2 + ν 3 band (ν 2 is the bending) were recorded at 25°C in aqueous solutions of TBA and TMAO over the 0-0.1 and 0-0.05 solute mole f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 39 publications
9
73
0
Order By: Relevance
“…This indicates that the water structuring induced at high concentration by proline and by TBA is comparable and more relevant than those caused by the presence of GB and TMAO. Since TBA self-aggregates at such concentrations [23], these results could be interpreted as suggesting that also for proline the water structure enhancement comes from self-aggregation, a mechanism previously hinted to explain experimental findings [9][10][11][12], such as anomalously high viscosity of concentrated aqueous solutions of proline. However, this view contrasts with the previous results about the proline hydration vs. solute concentration (Fig.…”
Section: Resultsmentioning
confidence: 52%
“…This indicates that the water structuring induced at high concentration by proline and by TBA is comparable and more relevant than those caused by the presence of GB and TMAO. Since TBA self-aggregates at such concentrations [23], these results could be interpreted as suggesting that also for proline the water structure enhancement comes from self-aggregation, a mechanism previously hinted to explain experimental findings [9][10][11][12], such as anomalously high viscosity of concentrated aqueous solutions of proline. However, this view contrasts with the previous results about the proline hydration vs. solute concentration (Fig.…”
Section: Resultsmentioning
confidence: 52%
“…The strong hydration of TMAO has been previously demonstrated in both experiments and simulations. [30][31][32][33][34][35] Urea is a nearly ideal solute in aqueous solution (in the molar scale); is smaller and correspondingly shows more modest correlations with water.…”
Section: Resultsmentioning
confidence: 99%
“…Since it has been found that in aqueous solution above, a threshold TBA concentration (x tba = 0.025) selfaggregation of TBA molecules takes place and in this selfaggregation process the methyl group of TBA participates [11,12,[15][16][17], so there must be some water loss around the hydrophobic methyl groups of TBA in order to facilitate this process. In this context, it is worth noting that the results of previous studies [16,17] also suggest that the dehydration of hydrophobic methyl groups of TBA serves as a sensitive indicator for monitoring TBA selfassociation.…”
Section: Structural Propertiesmentioning
confidence: 99%
“…But, despite their structural similarity, these solutes behave differently in dilute aqueous solutions. On the basis of experimental [1][2][3][4][5][6][7][8][9][10][11][12], simulation [13][14][15][16][17] and theoretical [18] evidence, it is known that TBA molecules tend to aggregate in dilute aqueous solution (at and above x tba ∼ 0.025) but TMAO does not [11,12,[15][16][17]. Furthermore, TBA and TMAO can influence systems of biological interest in very concentration [28].…”
Section: Introductionmentioning
confidence: 99%